Development of a Work Style Compass and Predicting Research Productivity of Agricultural Scientists - Paul, Sudipta; Vijayaragavan, K.; Singh, Premlata; Roy Burman, Rajarshi (International Journal of Bio-resource and Stress Management, 2023)
In light of increasing thrust of the public agricultural research system of India to enhance research productivity of its scientists, gauging scientists’ productivity and its personality correlates has been felt crucial. In this context, devising a simpler method to predict research productivity based upon individual work styles had been aimed in the present study. Randomly drawn two hundred agricultural scientists from different cadres of two differently performing agricultural institutes of the country constituted the sample of the study. A work style compass was designed by taking a measurement of individual work styles of the pooled sample after developing and pretesting Likert type scales. A research productivity index was developed to obtain productivity scores of scientists. A correlation and stepwise multiple regression analysis helped in deriving a suitable model to predict research productivity through the identified work style variables. The findings of the study confirmed a strong and positive relationship between research productivity and individual work styles. The results indicate to the crucial need for organizing work style sensitization workshops for the scientists and undertaking organization development interventions at individual institute level at regular intervals.